Temporal population variability in local forest communities has mixed effects on tree species richness across a latitudinal gradient. (7th November 2019) - Fung, Tak; Chisholm, Ryan A.; Anderson‐Teixeira, Kristina; Bourg, Norm; Brockelman, Warren Y.; Bunyavejchewin, Sarayudh; Chang‐Yang, Chia‐Hao; Chitra‐Tarak, Rutuja; Chuyong, George; Condit, Richard; Dattaraja, Handanakere S.; Davies, Stuart J.; et al.
Abstract: Among the local processes that determine species diversity in ecological communities, fluctuation‐dependent mechanisms that are mediated by temporal variability in the abundances of species populations have received significant attention. Higher temporal variability in the abundances of species populations can increase the strength of temporal niche partitioning but can also increase the risk of species extinctions, such that the net effect on species coexistence is not clear. We quantified this temporal population variability for tree species in 21 large forest plots and found much greater variability for higher latitude plots with fewer tree species. A fitted mechanistic model showed that among the forest plots, the net effect of temporal population variability on tree species coexistence was usually negative, but sometimes positive or negligible. Therefore, our results suggest that temporal variability in the abundances of species populations has no clear negative or positive contribution to the latitudinal gradient in tree species richness. Abstract : We quantified temporal population variability for tree species in 21 large forest plots and found much greater variability for higher latitude plots with fewer tree species. In addition, we used a fitted mechanistic model to show that among the forest plots, the net effect of temporal population variability on tree species coexistence was usually negative, but sometimes positive or negligible. Therefore, our results suggest that temporal population variability has no clear negative or positive contribution to the latitudinal gradient in tree species richness.